2022
DOI: 10.1021/acsaelm.2c01204
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Cut-In Voltage of a Silicon Carbide/p-Silicon Heterojunction Diode Using Femtosecond Laser Ablation

Abstract: We report on the fabrication of a low-cut-in voltage (a-SiC:H/Si) heterojunction diode using femtosecond laser ablation of silicon wafers in an octane environment. The femtosecond laser-induced plasma simultaneously reduces, carburizes, and hydrogenates the p-type silicon to develop a layer of hydrogenated silicon carbide (a-SiC:H) on top of the p-Si substrate. No reactive gases, source targets, dopants, or diffusion furnaces are required. The obtained current–voltage characteristics of the a-SiC:H/Si diode ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…This is due to the laser-induced oxygen plasma reacting with the topcoat and oxidizing it. Oxygen diffusion due to thermal and concentration gradients as well as melt hydrodynamic movement are associated phenomena for enhanced oxidation at higher accumulated fluence [70]. The O content in the interior of the MoO x layer may not be the same as that at the exterior surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the laser-induced oxygen plasma reacting with the topcoat and oxidizing it. Oxygen diffusion due to thermal and concentration gradients as well as melt hydrodynamic movement are associated phenomena for enhanced oxidation at higher accumulated fluence [70]. The O content in the interior of the MoO x layer may not be the same as that at the exterior surface.…”
Section: Resultsmentioning
confidence: 99%
“…Usually amorphous/nanocrystalline films are obtained after short laser-matter interaction. The crystallinity has been evidenced to improve with increasing accumulated fluence [70]. This is because higher accumulated fluence induces more reactive oxygen species [71], which not only enhance the MoO x content but also improve the crystallinity of the topcoat [72,73].…”
Section: Resultsmentioning
confidence: 99%
“…This might be attributed to the fact that the fast scanning speed for laser nanostructuring does not allow for the proper development of a crystalline structure. Therefore, an amorphous or a short-range nano-crystalline structure was observed [ 65 ]. Rajan et al [ 22 ] reported that fs laser structuring forms alumina with very small intensity peaks, thus depicting partially crystallinity.…”
Section: Resultsmentioning
confidence: 99%
“…The pulse fluence determines the ablation rate and the penetration depth [ 68 ], where considerable ablation takes place for fluence beyond the ablation threshold [ 30 ]. Similarly, the accumulated fluence determines the morphology and other properties of the surface features that emerge [ 65 ]. Excessive melt hydrodynamic movement and explosive material removal result from ablation at high fluence.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with other semiconductor materials such as Si and GaAs, Ge has a low coefficient of expansion, high temperature and pressure resistance, chemical stability, and high overload resistance. Ge also has good semiconductor industrial compatibility, as well as good narrow band gap and infrared transmission [3][4][5]. Thus, Ge is widely used in micro-and nano-device fabrication and related industry fields [6,7].…”
Section: Introductionmentioning
confidence: 99%